Diagnosis and Management of Sacroiliac Joint Dysfunction. (6th December 2017) - Ou-Yang, David C.; York, Philip J.; Kleck, Christopher J.; Patel, Vikas V.
Abstract : Symptoms that suggest that the sacroiliac joint (SIJ), as opposed to pathology of the lumbar spine or hip, may be a source of pain include pain with position changes, such as standing from a seated position or sitting on a hard surface. Radiation to the groin or Fortin area also suggest sacroiliac joint as a source. A constellation of findings, including pain referral patterns, provocative maneuvers, and response to injections, should be utilized when assessing SIJ pathology. While its effectiveness remains unsubstantiated, manipulation of the SIJ is noninvasive and warrants consideration as an initial treatment modality. The diagnostic validity of local anesthetic and/or corticosteroid injections is difficult to assess as the criteria for a positive response are not uniform in the literature, and evidence to support intra-articular injections for therapeutic purposes is weak. SIJ fusion appears to be emerging as an acceptable treatment for patients with recalcitrant SIJ dysfunction; however, only a few long-term outcome studies have been done. New minimally invasive fusion techniques appear to decrease the morbidity of open procedures with at least comparable outcomes.